High altitude renal syndrome: four elements or one source? - Lei Zhang; Erchao Feng; Sezhen Baima; Cangjue Laba; Lazhen Suolang; Ji Cang; Qing De (Renal Failure)
High Altitude Renal Syndrome (HARS) is a clinical syndrome characterized by polycythemia, hyperuricemia, hypertension, and albuminuria at high altitudes. This review emphasizes hypoxia-induced High Altitude Polycythemia (HAPC) as its core driver. In 2014, the 6th Qinghai International Conference on Mountain Medicine and High Altitude Physiology established international diagnostic criteria for HAPC (hemoglobin ≥210g/L in males, ≥190g/L in females). HAPC triggers systemic hypoxia, leading to hyperuricemia via uric acid overproduction and reduced renal excretion, hypertension from hemodynamic changes, and glomerular injury through erythrocytosis. Pathological mechanisms involve HIF-2α-mediated glomerular hypertrophy and podocyte damage. Treatment strategies target HAPC and downstream effects. Carbonic anhydrase inhibitors (e.g., acetazolamide) reduce hematocrit and improve oxygen saturation, but newer agents like methazolamide and dichlorphenamide offer equivalent efficacy with fewer side effects (e.g., reduced central nervous system toxicity). For severe cases, descending to lower altitudes remains the gold standard. Additional interventions include calcium channel blockers (nifedipine), urate-lowering drugs, and experimental therapies such as HIF-2α inhibitors (PT2385) and endothelin receptor antagonists (matitan). This analysis underscores HAPC as the primary etiology of HARS, advocating revised diagnostic criteria and treatment prioritization.